Adolescent's perception about the introduction of new cigarette packaging and plain packaging of cigarette packs: A qualitative study - Archana Bhat; K B Shilpashree; Archana Krishnamurthy; C Manjunath; R Shwetha; S Madhusudhan (Wolters Kluwer Medknow Publications, 2018)
Introduction: Larger health warning labels on cigarette packages were introduced in India in 2016 to more clearly inform consumers about the health risks associated with tobacco use. The aim of this study was to know the adolescent's perception on the introduction of new cigarette packaging and plain packaging of cigarette packs. Methodology: A qualitative study was carried out among adolescents aged 16-19 years. Eighteen participants were selected using purposive sampling technique. Three focus group discussions with the first group consisting of 6 smokers and the second and third groups consisted of 6 quit smokers and 6 nonsmokers were conducted. The data were later transcribed and analyzed using grounded theory approach. Results: Nearly all participants were aware of tobacco products, brand names, colors, and pictorial warnings on tobacco products. While the nonsmokers perceived fear was greater regarding warning and the pictorial messages, the current smoker's perceptions were unaffected by fear appeals. Almost all participants reported that new cigarette warning labels were more visible, informative, and scarier than the older ones. Conclusion: Positive impact of warning labels was seen among nonsmokers and few quit smokers whereas the current smoker's perceptions were unaffected.